The Intensive Care Unit Bundle Board: A Novel Real-Time Data Visualization Tool to Improve Maintenance Care for Invasive Catheters - Davis, Claire Leilani; Bjoring, Margot; Hursh, Jordyn; Smith, Samuel; Blevins, Cheri; Blackstone, Kris; Nicholson, Evie; Hoke, Tracey; Michel, Jonathan; Noth, Imre; Barros, Andrew; Enfield, Kyle (Applied Clinical Informatics, 2023)
Background Critically ill patients are at greater risk of healthcare-associated infections (HAIs). The use of maintenance bundles helps to reduce this risk but also generates a rapid accumulation of complex data that is difficult to aggregate and subsequently act upon.Objectives We hypothesized that a digital display summarizing nursing documentation of invasive catheters (including central venous access devices, arterial catheters, and urinary catheters) would improve invasive device maintenance care and documentation. Our secondary objectives were to see if this summary would reduce the duration of problematic conditions, that is, characteristics associated with increased risk of infection.Methods We developed and implemented a data visualization tool called the “Bundle Board” to display nursing observations on invasive devices. The intervention was studied in a 28-bed medical intensive care unit (MICU). The Bundle Board was piloted for 6 weeks in June 2022 and followed by a comparison phase, where one MICU had Bundle Board access and another MICU at the same center did not. We retrospectively applied tile color coding logic to prior nursing documentation from 2021 until the pilot phase to facilitate comparison pre- and post-Bundle Board release.Results After adjusting for time, other quality improvement efforts, and nursing shift, multiple linear regression demonstrated a statistically significant improvement in the completion of catheter care and documentation during the pilot phase (p < 0.0001) and comparison phase (p = 0.002). The median duration of documented problematic conditions was significantly reduced during the pilot phase (p < 0.0001) and in the MICU with the Bundle Board (comparison phase, p = 0.027).Conclusion We successfully developed a data visualization tool that changed ICU provider behavior, resulting in increased completion and documentation of maintenance care and reduced duration of problematic conditions for invasive catheters in MICU patients.
Keywords: data visualization tool; critical care medicine; nursing documentation; cognitive load; dashboard; quality improvement; Bundle Board